Comprehensive care: meanings for teachers and nursing students - Rosiane Filipin Rangel; Dirce Stein Backes; Silomar Ilha; Hedi Crecencia Heckler de Siqueira; Fernanda Demutti Pimpão Martins; Claudia Zamberlan (Universidade Federal do Ceará, 2017)
To understand the meaning of comprehensive care in the view of teachers and nursing students. Methods: qualitative research conducted with seven teachers and six students of the nursing course of a higher education institution. Data were collected using the Focal Group technique and subjected to thematic content analysis. The comprehensive care construct was used for this article as based on authors who talk with ownership of the theme. Results: the students perceive the comprehensive care as the subjective interaction with others respecting human uniqueness through a gradual construction in order to meet the apparent and non-apparent needs. Conclusion: teachers and students reported that comprehensive care depends on a network of actions and needs to be instigated since academic education.